Effectiveness of MPhil in Public Administration Programme - Shrestha, Buddhi Man (Nepalese Journal of Public Affairs, 2023)
The philosophical debate regarding the nature and scope of university education basically whether it is responsible to impart universal knowledge concentrating mainly in dissemination of knowledge than advancement of knowledge has been feathered out replacing by a significant role to be played by university for invention and innovation. In this context MPhil in public administration education program has been conducted by CDPA, TU with a view to advance the knowledge pertaining to public administration, policy and governance. It pays triggered attention to make students being able to conduct research activity independently in concerned areas which could contribute to heighten their competencies to compete in both global and Nepalese contexts. It seems ardent to know to usefulness of the context and content of the courses and enhancing the capacity of students in their work life situation. The objective of this paper is to explain the usefulness of the course content and institutional capacity of CDPA for conducting MPhil in public administration program effectively. For this, two hypotheses were constructed: usefulness of the course and contents; and institutional capacity of CDPA helps to enhance effectiveness of MPhil program. The mixed method of sequential explanatory strategy was adopted to conduct this research. Both the hypothesis has been tested based on chi square test in goodness of fit. The relationship between research variables is found to be positive. It is concluded that course and contents should be updated periodically and institutional capacity should be further strengthened. Thus, MPhil in public administration discipline has become vital for solving the problems of concerned areas.